Fracture Analysis of a Three-Dimensional Functionally Graded Multilayered - Rizov, V.I. (Проблемы прочности, 2018)
Delamination fracture behavior of the three-dimensional functionally graded multilayered crack lap shear (CLS) beam configuration was studied analytically in terms of the strain energy release rate with linear-elastic fracture mechanics methods. The CLS under consideration can consist of an arbitrary number of layers, each having different thickness and material properties. The material of each layer is functionally graded along its width, thickness, and length. A delamination crack is arbitrarily located along the beam height. The strain energy release rate was derived by analyzing its density in the beam cross section ahead and behind the crack front. It was additionally analyzed using the strain energy release rate was performed by using the beam strain energy for verification. The effect of the material gradient and crack location along the beam height on the delamination fracture behavior was evaluated.